Dampak Penggunaan Kecerdasan Buatan Artificial Intelligence dalam Praktik Akuntansi pada Bank Syariah Indonesia - Fenti Febriani (Banque Syar'i: Jurnal llmiah Perbankan Syariah, 2024)
Artificial Intelligence (AI) can be explained as a branch of computer science that focuses on developing computer systems capable of performing tasks that normally require human intelligence. The purpose of this study is to cover the path of using artificial intelligence in accounting practices in Islamic banks, as well as to identify the accounting profession. With a better understanding of the impact and implications, accounting professionals working in the banking sector can prepare themselves effectively for the changes that are taking place and take the necessary steps to optimize the benefits of using AI. The method used in this study is a qualitative descriptive method that focuses on individual observations and this research includes research that is a library research study. The results of this study are that this research identifies the impact of using AI in accounting practices in Islamic banks. The use of AI enables better market analysis and prediction, automation of financial reporting, and detection of anomalous patterns to combat fraud. However, new understanding and skills are needed for bank staff, as well as good regulations to address ethical challenges related to data privacy and algorithm transparency. This research is important for optimizing the application of AI technology in the Islamic banking sector.